Clinical, genetic, and experimental research of hyperphenylalaninemia - Chen, Anqi; Pan, Yukun; Chen, Jinzhong (Frontiers in Genetics, 2023)
Hyperphenylalaninemia (HPA) is the most common amino acid metabolism defect in humans. It is an autosomal-recessive disorder of the phenylalanine (Phe) metabolism, in which high Phe concentrations and low tyrosine (Tyr) concentrations in the blood cause phenylketonuria (PKU), brain dysfunction, light pigmentation and musty odor. Newborn screening data of HPA have revealed that the prevalence varies worldwide, with an average of 1:10,000. Most cases of HPA result from phenylalanine hydroxylase (PAH) deficiency, while a small number of HPA are caused by defects in the tetrahydrobiopterin (BH4) metabolism and DnaJ heat shock protein family (Hsp40) member C12 (DNAJC12) deficiency. Currently, the molecular pathophysiology of the neuropathology associated with HPA remains incompletely understood. Dietary restriction of Phe has been highly successful, although outcomes are still suboptimal and patients find it difficult to adhere to the treatment. Pharmacological treatments, such as BH4 and phenylalanine ammonia lyase, are available. Gene therapy for HPA is still in development.